Influence of Niobium Oxide on the Mechanical Properties of Hydroxyapatite - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2013)
The goal of this study is to produce and to investigate the mechanical and microstructural properties of composite materials made of hydroxyapatite, obtained from both natural sheep bone and commercial synthetic hydroxyapatite with niobium oxide addition (5 and 10 wt%). The samples were subjected to sintering at different temperatures between 1000 degrees C and 1300 degrees C. Microstructures and mechanical properties of sheep hydroxyapatite (SHA) and commercial synthetic hydroxyapatite (CSHA)-niobium oxide composites were investigated. The production of hydroxyapatite (HA) from natural sources is preferred due to economical reason. The aim of development of SHA and CSHA based niobium oxide composites is to improve mechanical properties of HA. The physical and mechanical properties were determined by measuring density, compression strength and Vickers microhardness (HV). Structural characterization was carried out with X-ray diffraction (XRD) and scanning electron microscopy (SEM) studies. In all composites, density values and mechanical properties increased with increasing sintering temperature. The increase of niobium oxide content in all composites showed better mechanical properties. Both of SHA and CSHA composites with at 1300 degrees C sintering temperature showed nearly the same compression strength value.
Keywords: Sheep hydroxyapatite; synthetic hydroxyapatite; mechanical properties; niobium oxide; COMPOSITES